Internationalisation of grocery retailing in the Global South: general conditions, formats and spatial expansion patterns of selected MNEs - Kulke, Elmar; Suwala, Lech (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
Grocery retail internationalisation in developing economies is a dynamic process that began just a decade ago. It was initially dominated by a North-South expansion of large retail MNE from Western Europe and North America. Hereby, only a limited number of grocery retail chains expanded to these markets, typically with formats such as hyper-/supermarkets. Super-/hypermarketisation is, however, no longer only a peculiarity and a dominant pattern of a North-South expansion, increasingly retail grocers from the Global South are both setting up similar types of stores in their home markets and gaining a foothold in neighbouring countries at the same time, leading to a new pattern of South-South expansion. Elaborating upon the crucial conditions for grocery retail internationalisation in general, the article analyses rationales, formats and selected companies that piloted this process, followed by a closer look upon the characteristics of spatial patterns in the expansion process. The latter were heavily influenced by spatial and socio-cultural proximity in the early days, whereas currently regionally and culturally more distant markets are penetrated.